2022
DOI: 10.3390/biology11081121
|View full text |Cite
|
Sign up to set email alerts
|

Giant Multinucleated Cells in Aging and Senescence—An Abridgement

Abstract: This review introduces the subject of senescence, aging, and the formation of senescent multinucleated giant cells. We define senescence and aging and describe how molecular and cellular senescence leads to organismal senescence. We review the latest information on senescent cells’ cellular and molecular phenotypes. We describe molecular and cellular features of aging and senescence and the role of multinucleated giant cells in aging-related conditions and cancer. We explain how multinucleated giant cells form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Our data show that myeloid‐derived cells (macrophages and giant cells) are the major inflammatory infiltrating cells expressing p16 and p21. Indeed, giant cell formation has been linked to senescence and has been suggested as a potential target in treatments promoting longevity (12). However, not all giant cells expressed p16 or p21, suggesting that not all of these cells were senescent.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that myeloid‐derived cells (macrophages and giant cells) are the major inflammatory infiltrating cells expressing p16 and p21. Indeed, giant cell formation has been linked to senescence and has been suggested as a potential target in treatments promoting longevity (12). However, not all giant cells expressed p16 or p21, suggesting that not all of these cells were senescent.…”
Section: Discussionmentioning
confidence: 99%
“…There remain numerous reports of its adverse effects on the phenotype of the cell or organism. Senescent cells are usually flattened and form giant multinucleated cells (GMCs), where metabolic deregulation, chromatin rearrangement, and resistance to apoptotic stimuli occur ( 19 ). Currently, more evidence has linked the tumor progression with the senescent microenvironment, which is mainly attributed to the SASP expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cofilin1 is associated with changes in cell morphology [ 14 ]. The nuclei of senescent ECs also undergo changes, such as increased nucleus size, multinucleation, and dissipation of the nuclear membrane [ 15 , 16 ].…”
Section: The Phenotype Of Senescent Ecsmentioning
confidence: 99%